2022
DOI: 10.3390/su141911913
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Waste to Energy Technologies for Municipal Solid Waste Management—Towards Achieving Sustainable Development Goals

Abstract: The Sustainable Development Goals (SDGs) play an essential role, emphasizing responsible resource use, production, and consumption, including waste management. In addition, SDG 3, 7, 11, 12, and 13 are directly/indirectly related to waste management. This study aims to determine a suitable waste-to-energy (WtE) technology in Chittagong City, Bangladesh, focusing on cleaner technology. Anaerobic digestion, gasification, incineration, and landfill gas (LFG) recovery were considered as possible alternatives. Tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…This section focuses on selecting sustainable MSW treatment technologies that will be productive for MSW regeneration. Relevant literature on sustainability factors such as environment, economy, technology and social indicators (Alam et al, 2022); the outcome of RM 1, RM 2 , and RM 3, which produced the prominent MSW components available within the study area, and the findings from background research preceding this current study, which identified potential enablers for MSWM transition to CE (Onungwe et al, 2023), gave insight on the suitable options to include incineration and anaerobic digestion under the thermochemical and biochemical techniques respectively (Agbejule et al, 2021;Farooq et al, 2021).…”
Section: Rm 4 -Circular Economy Transition Roadmap For Msw Utilizationmentioning
confidence: 91%
“…This section focuses on selecting sustainable MSW treatment technologies that will be productive for MSW regeneration. Relevant literature on sustainability factors such as environment, economy, technology and social indicators (Alam et al, 2022); the outcome of RM 1, RM 2 , and RM 3, which produced the prominent MSW components available within the study area, and the findings from background research preceding this current study, which identified potential enablers for MSWM transition to CE (Onungwe et al, 2023), gave insight on the suitable options to include incineration and anaerobic digestion under the thermochemical and biochemical techniques respectively (Agbejule et al, 2021;Farooq et al, 2021).…”
Section: Rm 4 -Circular Economy Transition Roadmap For Msw Utilizationmentioning
confidence: 91%
“…Among the different types of wastes converted to energy in incinerators, municipal solid waste (MSW), whose global consumption in 2022 was about 1.34 billion tons, has the highest Hg content ranging between 32.8 and 46222 μg kg −1 , as seen in Table 1 [ 38 ]. Consequently, waste combustion ranks third worldwide in Hg sources, as seen in Fig.…”
Section: Primary Mercury Sources: a Comprehensive Overviewmentioning
confidence: 99%
“…Gypsum, a raw material in cement manufacturing, is among the raw materials with the highest concentrations of Hg. Its global consumption in 2022 was about 150 million tons [ 38 ]. As seen in Table 1 , limestone is also critical for cement manufacturing, with Hg concentrations of about 16.2–33.4 μg kg −1 .…”
Section: Primary Mercury Sources: a Comprehensive Overviewmentioning
confidence: 99%
“…About 40% of the Municipal Solid Waste (MSW) produced globally is directed to landfills, while approximately 30% is disposed of in open dumps [3]. According to Sustainable Development Goal 11 (SDG 11) [4], proper municipal waste management is critically significant for advancing sustainability and ensuring the preservation of natural resources for future generations [5].…”
Section: Introductionmentioning
confidence: 99%